Structure, Types of Users and the Practices of Online-Social Networks as a Field of Political Practices - Ryabchenko, Natalia Anatolievna; Gnedash, Anna Aleksandrovna (International Review of Management and Marketing, 2015)
The aim of this study was to review of online-space as a field of political practices. Using the methods of mathematical modeling, network analysis, theory of the public sphere and the methodology of the social graph, the authors have substantiated the concept of online-space, web 2.0, web 3.0 from the position of Political Studies; investigated the practice of social and political mobilization of citizens and online-social networks around the world. There have also been identified and described these types of online-users of social networks as opinion leaders, sensors, implementors, readers, reputational players. “Opinion leaders” launch wave effects dissemination of information and, as a result, change the field of information and news. “Sensor” - people who collect relevant information within a particular semantic concept. “Implementors” - people who have run blogs, the role of implementer can be selected by the user both consciously and no. “Readers” - constitute the majority in online-space and in a single online-social network, they are constantly in the online-social networks and do not generate public posts. “Reputational players” - are the representatives of business and authority. Considered user types common to all online-social networks and do not depend on geographical reference and socio-political situation, but only different patterns of behavior and communication that these types of users form between them, which was confirmed by the authors in the course of research projects on a case study. Case-study “Blogger versus Garbage” describes the features of each type of users and the connection between them. Keywords: the Internet, online-social networks, network analysis, public policy, social graph, online-space, opinion leaders, sensors, implementors, readers, reputational players, political condensate, political mobilization JEL Classifications: Z13